Ca(2+) puffs originate from pre-established stable clusters of inositol trisphosphate receptors - Smith, Ian F. (2009)
Intracellular Ca(2+) signaling crucially depends upon the clustered organization of inositol trisphosphate receptors (IP(3)Rs) in the ER membrane that liberate Ca(2+) to generate local signals known as Ca(2+) puffs. Clusters of IP(3)Rs have been proposed to assemble rapidly in response to IP(3) itself. We tested this hypothesis by using flash photolysis of caged IP(3) in conjunction with high resolution Ca(2+) imaging to monitor the activity and localization of individual IP(3)Rs within intact mammalian cells. Our results indicate that puffs arising with latencies as short as 100–200 ms following photorelease of IP(3) already involve several (n ≥4) IP(3)R channels, and that this number does not subsequently grow. Moreover, single active IP(3)Rs show very limited motility, and stochastic simulations suggest that aggregation of IP(3)Rs at puff sites by a diffusional trapping mechanism would require many seconds. We thus find no evidence for rapid, IP(3)-regulated clustering of IP(3)Rs in intact cells, but instead conclude that puff sites represent pre-established, stable clusters of IP(3)Rs and that functional IP(3)Rs are not readily diffusible within the ER membrane.